The Effect of Attitudes, Subjective Norms, Behavioural Control, and Income on Intentions to Pay Agricultural Zakat with Zakat Literacy as a Moderating Variable - Fikri Anam; Furqonul Haq (FEBI UIN Sunan Kalijaga, 2022)
This study aims to determine the effect of attitudes, subjective norms, behavioral kontrol, and income on the intention to pay agricultural zakat with zakat literacy as a moderating variable. The sampling technique used is purposive sampling. The analytical method used was multiple linear regression and moderated regression analysis (MRA) with primary data types tested using SPSS 25. The number of samples in the study were 86 farmers in the Kebumen sub-district who owned rice fields and had reached the nisab. The results of the study prove that partially the variables of attitude, behavioral kontrol, and income have a significant positive effect on the intention to pay agricultural zakat. Meanwhile, the subjective norm variable has no significant effect on the intention to pay agricultural zakat. The results of the MRA test show that the zakat literacy variable moderate the effect of attitudes, subjective norms, and income. Meanwhile, the zakat literacy variable failed to moderate the effect of behavioral kontrol on the intention to pay agricultural zakat.)